2014
DOI: 10.1002/cbdv.201400087
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Stems of Excoecaria acertiflia

Abstract: Six new compounds, including two diterpenoids excocarinols F and G (1 and 2, resp.), two carotane (daucane) sesquiterpenoids excoecafolinols A and B (3 and 4, resp.), one lignanoid compound, excoecanol A (5), and one simple phenol, excoecanol B (6), together with 17 known compounds, were isolated from the BuOH extract of Excoecaria acerifolia Didr. stems. Their structures were elucidated through the analysis of the spectroscopic data. The AChE-inhibitory activities of 17 compounds were evaluated and revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compounds 1–5 were all tested for their AchE-inhibitory activity by Ellman’s Method as described before [13]. As a result, compounds 1–3 (at the concentration of 94 nM) showed moderate activity with the AChE inhibit index (AII) 68.96 ± 0.19, 57.8 ± 0.11 and 37.55 ± 0.12 % at 94 nM, respectively, compared with the negative control (AII 8.94 ± 0.09%) and positive control (tacrine with AII 79.8 ± 0.20 %, 9.4 nM) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 1–5 were all tested for their AchE-inhibitory activity by Ellman’s Method as described before [13]. As a result, compounds 1–3 (at the concentration of 94 nM) showed moderate activity with the AChE inhibit index (AII) 68.96 ± 0.19, 57.8 ± 0.11 and 37.55 ± 0.12 % at 94 nM, respectively, compared with the negative control (AII 8.94 ± 0.09%) and positive control (tacrine with AII 79.8 ± 0.20 %, 9.4 nM) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The AchE-inhibitory activity of the compounds was tested as described by Ellman’s Method in the literature [13,14]. The mixed reaction solution contained test compound soln.…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that various parts of the plant namely roots, leaves, stems, barks, fruits, flowers and twigs are used for medicinal purpose, some of them are used as for food. [3] Phytochemical survey reveals that wide range of secondary metabolites alkaloids, [4] Coumarins, [5] Pyrano-coumarins, [6] limnoids, [7] essential oils, [8] insecticides [9] were isolated from the different species of Rutaceous plants. Pharmacological survey reveals that researchers around the world identified anticancer, [10] antibacterial, [7] antifungal, [7] anti-HIV, [11] immunomodulatory, [12] antinociceptive, [13] antimalarial, [14] insecticidal [9] activities of extracts and isolated compounds.…”
Section: Introductionmentioning
confidence: 99%
“…1 This class of diterpenes can be derived from the original core by substitution, hydroxylation, acetylation, rearrangement, bromination, and ring expansion reactions. 2 Since the isolation of pimaric acid, the rst example of this class, in 1839, 3 pimarane diterpenoids have attracted considerable interest due to their remarkable structural diversity and great antimalarial, 4 antibacterial, 5 antifungal, 6 antiviral, 7,8 phytotoxic, 6 cytotoxic, [9][10][11][12] AChE-inhibitory, 13 and anti-inammatory activities. 14 Sarcosomataceous fungi (Ascomycota), usually known as degraders of wood or as pathogens, 15 have been reported to produce spirobisnaphthalenes, 16,17 lactones, 15,[18][19][20][21] naphthalones, 21 cyclohexenones, 22 and isocoumarins.…”
Section: Introductionmentioning
confidence: 99%